Replacing "Alkyl" with "Aryl" for inducing accessible channels to closed pores as plateau‐dominated sodium‐ion battery anode. Issue 3 (20th May 2022) - Shao, Wenlong; Cao, Qi; Liu, Siyang; Zhang, Tianpeng; Song, Zihui; Song, Ce; Weng, Zhihuan; Jian, Xigao; Hu, Fangyuan
Abstract: Hard carbons are promising anodes for sodium‐ion batteries. However, there is still considerable controversy regarding the sodium storage behaviors in hard carbons, which are mainly attributed to the varied precursors, confused pyrolysis mechanism, and different characterization methods. Herein, benefiting from the flexible molecular structure of polymers, a series of hard carbons with carefully tuned microstructures are fabricated by adjusting the ratio of aryl and alkyl groups in the epoxy resins. The results of dynamic mechanical analysis, in‐situ Fourier transform infrared spectra, and synchronous thermal gravimetric‐infrared spectrum‐gas chromatography/mass spectrometry reveal that replacing the alkyl with aryl groups in the resin can enhance the crosslink density, inhibit the degradation and rearrangement process, and further lead to a more disordered microstructure. In addition, it is suggested that accessible channels provided by sufficiently wide interlayer spacing are necessary for closed pore filling. The optimized anode delivers a high capacity of 375 mAh/g in half cell with an initial Coulombic efficiency of 80.61%, and an energy density of 252 Wh/kg is attained in full cell. Finally, a reliable relationship among precursor–pyrolysis mechanism–structure–performance is established, and the sodium storage mechanism of "adsorption–insertion–pore filling" is well proved. Abstract : The composition of precursors is precisely controlled based on the flexible molecular structure of polymers. Replacing the alkyl with aryl groups can enhance the crosslink density, inhibit the two‐step degradation and rearrangement process, and lead to hard carbons with more accessible channels to internal pores, thereby resulting in an extended plateau region during discharging.